Teknologi Mitigasi Gas Rumah Kaca Di Lahan Rawa Pasang Surut - Wahida Annisa; Achmad Rachman (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Annisa, et al.Â Technologies for Mitigating Greenhouse Gas Emissions on Tidal Swamp Land. JLSO 5(2):178-188.Utilization of swamps for agricultural development is a strategic choice in an effort to offset the decrease in productive land in Java due to conversion of land functions from agriculture to non-agriculture. The properties of land in swamplands is a major limiting factor that causes low productivity of swamp land. The development of agriculture in swamplands often has a negative impact on land and environment, due to inappropriate landl management. One of the environmental impacts in swampland development is carbon emissions. Carbon emissions can be reduced through the use of appropriate soil ameliorant and water management within the swamp hydrological area. Both approaches are important not only to mitigate greenhouse gas emissions but also to increase swampland agriculture productivity.